Gay Liberation and the Politics of the Self in Postwar America - Serby, Benjamin (2020)
This dissertation broadens the scope of our understanding of the gay liberation movement in the United States by situating it in the wider intellectual, cultural, and political currents of the three decades following the Second World War. By examining the personal papers of key gay and lesbian activists in the late 1960s and early 1970s, as well as the print media that disseminated their ideas to a nationwide public, it demonstrates the profound influence of the social thought of the 1940s and 1950s on the movement, and traces that reception by way of social movements: in particular, the new left, radical feminism, and the youth counterculture. It shows that midcentury theorists in a range of disciplines offered a distinct way of understanding the relationship between society and the self that inverted established hierarchies, thus enabling gay liberation activists and writers to anchor their vision of social transformation in the reconstruction of sexuality, gender, and the psyche.